Mapping of fatty acid composition with free‐breathing MR spectroscopic imaging and compressed sensing. (3rd January 2020) - Rioux, James A.; Hewlett, Miriam; Davis, Christa; Bowen, Chris V.; Brewer, Kimberly; Clarke, Sharon E.; Beyea, Steven D.
Abstract : Nonalcoholic fatty liver disease (NAFLD) is a growing health problem, and a major challenge in NAFLD management is identifying which patients are at risk of progression to more serious disease. Simple measurements of liver fat content are not strong predictors of clinical outcome, but biomarkers related to fatty acid composition (ie, saturated vs. unsaturated fat) may be more effective. MR spectroscopic imaging (MRSI) methods allow spatially resolved, whole‐liver measurements of chemical composition but are traditionally limited by slow acquisition times. In this work we present an accelerated MRSI acquisition based on spin echo single point imaging (SE‐SPI), which, using appropriate sampling and compressed sensing reconstruction, allows free‐breathing acquisition in a mouse model of fatty liver disease. After validating the technique's performance in oil/water phantoms, we imaged mice that had received a normal diet or a methionine and choline deficient (MCD) diet, some of which also received supplemental injections of iron to mimic hepatic iron overload. SE‐SPI was more resistant to the line‐broadening effects of iron than single‐voxel spectroscopy measurements, and was consistently able to measure the amplitudes of low‐intensity spectral peaks that are important to characterizing fatty acid composition. In particular, in the mice receiving the MCD diet, SE‐SPI showed a significant decrease in a metric associated with unsaturated fat, which is consistent with the literature. This or other related metrics may therefore offer more a specific biomarker of liver health than fat content alone. This preclinical study is an important precursor to clinical testing of the proposed method. MR‐based quantification of fatty acid composition may allow for improved characterization of non‐alcoholic fatty liver disease. A spectroscopic imaging method with appropriate sampling strategy allows whole‐liver mapping of fat composition metrics in a free‐breathing mouse model. Changes in metrics like the surrogate unsaturation index (UIs) are visible in mice receiving a diet which induces fat accumulation in the liver, as compared to a normal diet; such metrics may prove useful in future clinical studies of liver disease. Abstract : MR‐based quantification of fatty acid composition may allow for improved characterization of non‐alcoholic fatty liver disease. A spectroscopic imaging method with appropriate sampling strategy allows whole‐liver mapping of fat composition metrics in a free‐breathing mouse model. Changes in metrics like the surrogate unsaturation index (UIs) are visible in mice receiving a diet which induces fat accumulation in the liver, as compared withto a normal diet; such metrics may prove useful in future clinical studies of liver disease.